Solvent-Reversible Addition of Alkyne C-H Bonds to Water-Soluble NHC Platinum(0) Complexes - Baquero, Edwin A. (2017)
Oxidative addition of CH3I and alkynes to the platinum(0) complex [Pt(AE)NHC] (1), in which the NHC ligand is a sulfonated version of the IPr ligand (1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene) and AE is diallyl ether, is reported. Reaction with the haloalkane affords the iodomethyl complex [PtI(Me)NHC] (2), whereas the addition of alkynes via C(sp)-H bond activation leads to the corresponding new water-soluble hydride (NHC)PtII complexes 3 and 4. Complexes 3 and 4 were found to be moderately stable in water, displaying an interesting behavior in this solvent. Thus, in the presence of the corresponding olefin, the reaction can be reversible under mild conditions, thus allowing the formation of diolefinic (NHC)Pt0 complexes 1, 5, and 6, with elimination of the alkyne.